Medical treatment prior to micro-TESE - Sujoy Dasgupta; Thanh Sang Le; Amarnath Rambhatla; Rupin Shah; Ashok Agarwal (Asian Journal of Andrology)
Except in cases of hypogonadotropic hypogonadism, the use of medical therapy before microsurgical testicular sperm extraction (micro-TESE) is controversial. In some studies, hormone therapy has been shown to improve the possibility of sperm retrieval during micro-TESE and even lead to the presence of sperm in the ejaculate in some cases, thereby obviating the need for micro-TESE. However, their routine use before micro-TESE in cases of nonobstructive azoospermia (NOA) being associated with hypergonadotropic hypogonadism and eugonadism (normogonadotropic condition) has not been supported with robust evidence. In this review, we discuss different types of medical therapy used before micro-TESE for NOA, their risks and benefits, and the available evidence surrounding their use in this setting.